2010
DOI: 10.1007/s11869-010-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial representation in the development of a LUR model for Ottawa, Canada

Abstract: A land use regression (LUR) model for the mapping of NO2 concentrations in Ottawa, Canada was created based on data from 29 passive air quality samplers from the City of Ottawa’s National Capital Air Quality Mapping Project and two permanent stations. Model sensitivity was assessed against three spatial representations of population: population at the dissemination area level, population at the dissemination block level and a dasymetrically derived population representation. A spatial database with land use, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The predicted NO 2 surfaces were similar with respect to concentrations in peripheral hotspot areas as both models included population density and industrial areas as predictors. However, the addition of intersection density in this study appeared to improve upon the overall model fit and suggested that NO 2 concentrations in central areas of Ottawa where the street network is characterized by higher connectivity were underestimated by Parenteau and Sawada (2012). Wheeler et al (2008) found that their NO 2 LUR model in Windsor explained less spatial variation than a previous model by Luginaah et al (2006) and attributed this to a lack of traffic data.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The predicted NO 2 surfaces were similar with respect to concentrations in peripheral hotspot areas as both models included population density and industrial areas as predictors. However, the addition of intersection density in this study appeared to improve upon the overall model fit and suggested that NO 2 concentrations in central areas of Ottawa where the street network is characterized by higher connectivity were underestimated by Parenteau and Sawada (2012). Wheeler et al (2008) found that their NO 2 LUR model in Windsor explained less spatial variation than a previous model by Luginaah et al (2006) and attributed this to a lack of traffic data.…”
Section: Discussionmentioning
confidence: 67%
“…The study area also offered an opportunity to improve upon a previous NO 2 LUR model for Ottawa by using measurements from more sampling locations and two seasonal monitoring campaigns rather than just fall measurements (Parenteau and Sawada, 2012). Parenteau and Sawada (2012) found that population densities calculated based on dissemination block (DB) data rather than the traditional dissemination area level improved the prediction of NO 2 . The current study computed population and predictor variables from DB level data, but additionally assessed the influence of industrial point sources and intersection density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of that model are published elsewhere [47]. The model, which included data on the road network, population, green spaces and industrial land-use, yielded an R 2 of 0.8055.…”
Section: Methodsmentioning
confidence: 99%